2010
DOI: 10.1016/j.cub.2010.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Subconscious Motor Control Predicted by GABA Concentration in SMA

Abstract: Subliminal visual stimuli affect motor planning, but the size of such effects differs greatly between individuals. Here, we investigated whether such variation may be related to neurochemical differences between people. Cortical responsiveness is expected to be lower under the influence of more of the main inhibitory neurotransmitter, GABA. Thus, we hypothesized that, if an individual has more GABA in the supplementary motor area (SMA)--a region previously associated with automatic motor control--this would re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
139
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(167 citation statements)
references
References 47 publications
17
139
1
Order By: Relevance
“…The authors assumed that when the participants were awaiting a target, the presence of the non-target stimulus (more often a mask) just after the prime might inform the system that the ongoing action was possibly premature and wrongly prepared. Note that Eimer and colleagues as well as Jaśkowski and colleagues agreed that the NCE is the result of a purely motor inhibition, which is presumably caused by the SMA (Boy et al, 2010a;Boy, Husain, Singh, & Sumner, 2010b;Sumner et al, 2007). According to this general view, a positive perceptual compatibility effect co-occurring with a negative motor compatibility effect might be observed at long Mask-Target SOAs when the prime is not sufficiently masked, because the perceptual trace would be preserved over time but would not be the focus of inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The authors assumed that when the participants were awaiting a target, the presence of the non-target stimulus (more often a mask) just after the prime might inform the system that the ongoing action was possibly premature and wrongly prepared. Note that Eimer and colleagues as well as Jaśkowski and colleagues agreed that the NCE is the result of a purely motor inhibition, which is presumably caused by the SMA (Boy et al, 2010a;Boy, Husain, Singh, & Sumner, 2010b;Sumner et al, 2007). According to this general view, a positive perceptual compatibility effect co-occurring with a negative motor compatibility effect might be observed at long Mask-Target SOAs when the prime is not sufficiently masked, because the perceptual trace would be preserved over time but would not be the focus of inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The supplementary motor area (SMA) plays a pivotal role in complex hand movements such as sequential motor tasks (Shima and Tanji 1998), bimanual coordination (Zhuang et al 2005), and motor inhibition (Boy et al 2010). In addition to neuroimaging and animal studies, researches using transcranial magnetic stimulation (TMS) have provided evidence of SMA involvement in various motor tasks by stimulating SMA non-invasively in humans (MeyerLindenberg et al 2002;Steyvers et al 2003;Tanaka et al 2010;Verwey et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous studies examining the role of RT fluctuations on the negative CE (Eimer, 1999;Schlaghecken & Eimer, 2000;Verleger et al, 2004), we used masks composed by random lines to ensure that the NCE reflects automatic motor inhibition and not object-updating (Lleras & Enns, 2004). Prior studies using random line masks have already shown that the mask-target SOA modulates automatic inhibition of the irrelevant prime activation (Aron et al, 2003;Boy, Evans, et al, 2010;Seiss & Praamstra, 2006). More specifically, these studies showed that short SOAs (0 -40 ms) were associated with a PCE, while long SOAs (100 -150 ms) were associated with an NCE.…”
Section: Discussionmentioning
confidence: 99%